Abrasion Disaster Mitigation Efforts at Naras Beach, North Pariaman District - Zuriyani, Elvi; Juita, Erna; Irwan, Irwan; Ulni, Arie Zella Putra; Despica, Rika (Universitas Veteran Bangun Nusantara, 2023)
Abrasion is a process of eroding the beach by sea waves and ocean currents which are destructive. In the coastal area of Naras, North Pariaman District, there was abrasion which had an impact on the people in the coastal area. The purpose of this study was conducted to determine the form of disaster mitigation carried out by the community in the Naras coastal area. This research was conducted using a qualitative descriptive approach. Data collection techniques were carried out by field observations, documentation and interviews with the community in the Naras Beach area. Efforts made by the community and government against coastal abrasion are by making embankments from sand, building wave-retaining rock grips, building T-type groins, and planting mangroves.